2021
DOI: 10.1021/acs.energyfuels.1c02590
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Semimetal-Boosted Electron Transfer, Nitrogen Adsorption, and Nitrogen Photoreduction Activity of Bi/g-C3N4 Nanosheets

Abstract: Nitrogen photoreduction is a promising ammonia production technology since it can be carried out at the atmospheric pressure by merely utilizing the abundant solar energy. However, the low conversion efficiency is still a big challenge for practical applications. In this work, Bi-decorated g-C 3 N 4 nanosheets are successfully prepared by an in situ solvothermal method. The ultraviolet−visible diffuse reflection spectrum shows that Bi decoration conspicuously enhances the visible light absorption because of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…It was reported that the bismuth oxide thin layer was easily formed on the surface of metallic bismuth to prevent further oxidation of bismuth metal. 35 This phenomenon provided a reasonable explanation for the existence of two pairs of characteristic peaks in different positions in BiCCN-15 and BiCN-15, indicating that bismuth metal has been successfully decorated on the catalyst surface.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…It was reported that the bismuth oxide thin layer was easily formed on the surface of metallic bismuth to prevent further oxidation of bismuth metal. 35 This phenomenon provided a reasonable explanation for the existence of two pairs of characteristic peaks in different positions in BiCCN-15 and BiCN-15, indicating that bismuth metal has been successfully decorated on the catalyst surface.…”
Section: Resultsmentioning
confidence: 64%
“…Thus, metallic-Bi-decorated carbon nitride materials have great potential in the degradation of wastewater. However, the synthesis process of Bi metal is complex and generally requires a reductant to reduce Bi(NO 3 ) 3 , 35,36 which is not conducive to environmental protection. Therefore, an environmentally-friendly and simple method for preparing C 3 N 4 photocatalysts decorated with metallic Bi nanoparticles needs to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, morphological control of catalysts is an ideal method to increase the active catalytic sites, which is helpful to improve the photocatalytic nitrogen fixation performance. For example, nanosheets, nanotubes, and mesoporous structures were prepared for g-C 3 N 4 catalysts; , two-dimensional (2D) nanosheets and three-dimensional (3D) microspheres were prepared for BiOCl-based photocatalysts . It was found that the adjustment of the morphology and size of the catalyst can effectively promote the separation and interfacial transport of photogenerated electrons and holes, which can weaken the bond energy of the NN triple bond to a certain extent, thus achieving the purpose of nitrogen activation.…”
Section: Morphology Controlmentioning
confidence: 99%
“…[28] In addition, the other peaks at 158.1 and 163.3 eV were indexed to Bi 3+ (Figure 3d), probably because the metallic Bi could be oxidized by O 2 in the air to form Bi 2 O 3 on the surface of Bi. [28,34] It's worth noting that the deposition of Bi onto the surface of COF-TaTp, N 1s, and O 1s peaks of 5% Bi/COF-TaTp were shifted to higher and lower binding energies respectively. These results suggested that strong interaction occurred between the Bi and N, O of COF-TaTp.…”
Section: Photocatalysts Synthesis and Characterizationmentioning
confidence: 99%